Dyglosja w historii greckiego języka prawa - Gortych, Karolina (Investigationes Linguisticae, 2008)
A diglossia is a typical phenomen for Greek language from the beginning of existence the modern Greek state (1830). The Greeks spoke “two languages” which were attributed to definited social activities. Language of Law was very archaic type of language which lied on the idea of purification of the language which exactly was idea of “katharevousa” – an artificial language system. This situation lasted till the year 1976. In the same time, simultaneously a natural, living language – “dimotiki” developed. It was a language which was spoken by the Greeks out of public institutions and it developed and existed independently of official language of Greek State what was exactly “katharevousa”. For about 150 years two antithetic linguistic ideas (“katharevousa”and “dimotiki”) were in struggle for primacy and for recognition as an official language in Greek state. That contradiction which was language question (”glossiko zitima”) was terminated by the Constitution of 1976 according to which “katharevousa” stopped being official language of the state and of the law. The mentioned Constitution as a main statutory act and a basis of all rights in the State was written in a language lied on “dimotiki”. In these circumstances the language of law changed too. This presentation has an aim to point some demotic solutions which were used in the process of metaglossy of statutory texts. Presented here examples base on unified text of the Constitution of 1976 with its later changes and on the text of the last constitution written in “katharevousa” i.e. Constitution of 1968. Summary of presented ideas and estimation to what degree Greek language of law based on “katharevousa” differed from the present Greek language of Law, makes up the conclusion of the paper and simultaneously it will underline profile of two mentioned types of language which coexisted in the period of diglossy.